El aprendizaje de la creatividad en las facultades de comunicación - Jiménez, Silvia (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
We consider necessarily to endow to the journalists and future professionals of the theoretical, practical and human knowledges to implement the development of his (her,your) creativity, a quality capable of being improved. To the powers of communication the labor corresponds (fits) to them of giving knowledges on creativity in order that the professionals assume it as a fundamental value. And everything, because the hearing will claim originality and because it (he, she) recognizes the success of the professionals who manage to differentiate his (her, your) information with an own (proper) style. Also in the powers of communication technologies (skills) of stimulation should be given to unfuse skills and creative skills that provide habits and strategies to the students. To promote attitudes and creative qualities in the pupils will help them to find solutions before the problems and to have an opened and tolerant disposition (regulation) opposite to the phenomenon, besides providing them with confidence in if same to overcome the barriers.